2012
DOI: 10.1371/journal.ppat.1002724
|View full text |Cite
|
Sign up to set email alerts
|

The Wor1-like Protein Fgp1 Regulates Pathogenicity, Toxin Synthesis and Reproduction in the Phytopathogenic Fungus Fusarium graminearum

Abstract: WOR1 is a gene for a conserved fungal regulatory protein controlling the dimorphic switch and pathogenicity determents in Candida albicans and its ortholog in the plant pathogen Fusarium oxysporum, called SGE1, is required for pathogenicity and expression of key plant effector proteins. F. graminearum, an important pathogen of cereals, is not known to employ switching and no effector proteins from F. graminearum have been found to date that are required for infection. In this study, the potential role of the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
130
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 63 publications
4
130
0
Order By: Relevance
“…The white-opaque switching model has wide-ranging significance. Although the impact of white-opaque switching on C. albicans virulence is unclear (42,43), Wor1 orthologs in other fungal pathogens of mammals (44) and plants (45)(46)(47) are clearly determinants of virulence. Meta-analysis has shown that the architecture and stability of the white-opaque transcriptional circuit share many properties with those of the Oct4 circuit, which governs the pluripotency and differentiation of mouse embryonic stem cells (36).…”
mentioning
confidence: 99%
“…The white-opaque switching model has wide-ranging significance. Although the impact of white-opaque switching on C. albicans virulence is unclear (42,43), Wor1 orthologs in other fungal pathogens of mammals (44) and plants (45)(46)(47) are clearly determinants of virulence. Meta-analysis has shown that the architecture and stability of the white-opaque transcriptional circuit share many properties with those of the Oct4 circuit, which governs the pluripotency and differentiation of mouse embryonic stem cells (36).…”
mentioning
confidence: 99%
“…Gti1 plays a role in regulation of gluconate uptake in Schizosaccharomyces pombe [19]. The Wor1 homologs from several necrotrophic plant pathogens are all important for pathogenesis and toxin synthesis [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…1A), including the human pathogens Candida albicans (1-3), Histoplasma capsulatum (4), and Cryptococcus neoformans (5) and several plant pathogens (6)(7)(8)(9). In C. albicans, Wor1 controls the process of white-opaque switching and mating (1)(2)(3), and it has a key role in promoting commensalism (10).…”
mentioning
confidence: 99%